A cost–utility analysis of dulaglutide versus insulin glargine as third-line therapy for Type 2 diabetes in Canada. (15th January 2019) - Pollock, Richard F; Norrbacka, Kirsi; Cameron, Chris; Mancillas-Adame, Leonardo; Jeddi, Mark
Aim: The prevalence of Type 2 diabetes in Canada is estimated to be 7.6% and rising. Given the substantial economic burden associated with Type 2 diabetes treatment, optimizing healthcare expenditure is extremely important. In the present analysis, we evaluated the cost–effectiveness of dulaglutide 1.5 mg, a once-weekly glucagon-like peptide 1 agonist as third-line therapy relative to insulin glargine from the perspective of a Canadian healthcare payer.Methods: A patient-level cost-utility model of Type 2 diabetes was developed to capture seven microvascular and macrovascular complications and severe and nonsevere hypoglycemia. Cohort characteristics and the relative efficacy of dulaglutide 1.5 mg and insulin glargine were derived from the AWARD-2 head-to-head trial, which was identified by systematic literature review. Cost data were derived from Canadian sources and expressed in 2016 Canadian dollars (CAD), and future cost and quality-adjusted life expectancy (QALE) estimates were discounted at 1.5% per annum. One-way and probabilistic sensitivity analyses were conducted.Results: Based on the AWARD-2 trial, relative to insulin glargine, dulaglutide 1.5 mg was projected to increase QALE by 0.38 quality-adjusted life years and increase costs by CAD 19, 773, resulting in an incremental cost–effectiveness ratio of CAD 52, 580 per quality-adjusted life year gained.Conclusion: A computer simulation analysis showed that dulaglutide 1.5 mg would likely be cost-effective relative to insulin glargine in patients with Type 2 diabetes inadequately controlled on metformin and sulfonylurea in Canada.